Pengaruh Kebijakan Subsidi Pupuk dan Karakteristik Petani Terhadap Tingkat Kesejahteraan Petani Tembakau - Afsah Novita Sari; Suwandri Nur Alif; Nisa Ayunda (Universitas PGRI Adi Buana Surabaya, 2023)
Farmer welfare is a condition of a farmer in a prosperous, healthy and peaceful condition without social jealousy in the community. However, this is difficult to materialize for farmers because of a number of factors, namely the ineffective and inefficient fertilizer subsidy policy with farm needs and the different characteristics of farmers in conducting farming.The purpose of this study was to analyze the level of welfare of tobacco farmers in Jombang Regency measured by the large farmer exchange rate (NTP) with several variables including the fertilizer subsidy policy variable, and the farmer characteristics variable.From statistical testing using ordinal logistic regression. The research data was obtained with 123 questionnaires distributed in Sawahan Hamlet Sumbergondang Village, Kabuh District, Jombang Regency.From the partial test, it was explained that the variables which were made into research did not significantly influence the farmer exchange rate (NTP). The results of the coefficient of determination show the results of the coefficient of determination Nagelkerke of 0.900 or 90.0%. It means that the independent variable (fertilizer subsidy policy, and the characteristics of farmers) affects the farmer exchange rate (NTP) of 90.0% while 10.0% is influenced by other factors not included in this research variable.